L’incarnation comme « conversation » selon saint Thomas d’Aquin - Durand, Emmanuel (Revue des sciences philosophiques et théologiques, 2018)
The motif of conversation is surprisingly rich in the semantic and theology of Saint Thomas Aquinas. After a search for patristic antecedents and the identification of a potential source, this study proposes a cross-linking of the question De modo conversationis Christi (Summa theol. IIIa, q. 40) with other texts on Incarnation or charity. Two doctrinal assets emerge from the research undertaken here. First, Christ's conversation with his contemporaries, even to the point of commensality with sinners, corresponds to the full manifestation of the mystery of the Incarnation, in terms of “expressed reality”. Secondly, the register of conversation qualifies both the friendship between God and man, made possible by charity, and the type of relationship that Christ had with his contemporaries in the fulfilment of his mission. Such an affinity of language reflects a deeper reality: Christ the man has singularly brought God closer to humanity, so that, through his mediation, the covenant may be actualized among them, under the astonishing modes of conversation, proximity and intimacy.